A Critical Revision of the Empirical Literature on Chinese Outward Investment: A New Proposal - Rodríguez, Carlos; Bustillo, Ricardo (Panoeconomicus, 2011)
Research on China’s role in the globalisation of economic activity focuses mainly on its involvement in trade and on its competitiveness as a manufacturing location for foreign investors. However, since the mid-1990s China’s outward foreign direct investment (OFDI) has become an important part of its integration into the global economy. This dimension is poorly understood, and few empirical studies about the drivers behind Chinese OFDI have been published thus far. After reviewing critically the empirical literature, which provides ambiguous results about the explanatory power of some of the large list of determinants put forward, we aim to provide a more accurate description of the motives behind Chinese OFDI. Using a panel data approach for the period 1995 to 2009 and for a large host country sample, we identify some key drivers. We find that host market size, natural resources and FDI openness are of paramount relevance. However, the asset seeking hypothesis is not confirmed. Key words: China, Outward foreign direct investment, Multinational enterprises. JEL: F15, F23.